Question
upstudy study bank question image url

2) \( \log _{3}(5-x)+\log _{3}(-1-x)=(3) ; \log _{3} 3 \)

Ask by Weber Reyes. in Kazakhstan
Feb 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = -4 \)

Solution

Давайте решим уравнение шаг за шагом. Дано уравнение: \[ \log_{3}(5-x) + \log_{3}(-1-x) = 3 \] Сначала воспользуемся свойством логарифмов, которое гласит, что сумма логарифмов равна логарифму произведения: \[ \log_{3}((5-x)(-1-x)) = 3 \] Теперь, чтобы избавиться от логарифма, возведем обе стороны уравнения в степень 3: \[ (5-x)(-1-x) = 3^3 \] Это упрощается до: \[ (5-x)(-1-x) = 27 \] Теперь раскроем скобки: \[ -5 - 5x + x + x^2 = 27 \] Упрощаем уравнение: \[ x^2 - 4x - 5 = 27 \] Переносим 27 в левую часть: \[ x^2 - 4x - 32 = 0 \] Теперь решим это квадратное уравнение с помощью формулы корней: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] где \( a = 1, b = -4, c = -32 \). Подставим значения: \[ x = \frac{4 \pm \sqrt{(-4)^2 - 4 \cdot 1 \cdot (-32)}}{2 \cdot 1} \] Теперь вычислим дискриминант: \[ D = 16 + 128 = 144 \] Теперь подставим дискриминант в формулу: \[ x = \frac{4 \pm 12}{2} \] Это дает два решения: 1. \( x = \frac{16}{2} = 8 \) 2. \( x = \frac{-8}{2} = -4 \) Теперь проверим, подходят ли эти значения для исходного уравнения, учитывая ограничения логарифмов: 1. Для \( x = 8 \): - \( 5 - 8 = -3 \) (недопустимо, так как логарифм от отрицательного числа не определен) - \( -1 - 8 = -9 \) (недопустимо) 2. Для \( x = -4 \): - \( 5 - (-4) = 9 \) (допустимо) - \( -1 - (-4) = 3 \) (допустимо) Таким образом, единственное допустимое решение: \[ x = -4 \] Ответ: \( x = -4 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( \log _{3}(5-x)+\log _{3}(-1-x)=3 \), we can first use the property of logarithms that states \( \log_b a + \log_b c = \log_b(ac) \). This means we can combine the left side: \[ \log_{3}[(5-x)(-1-x)] = 3 \] Next, we can exponentiate both sides using 3 as the base to eliminate the logarithm: \[ (5-x)(-1-x) = 3^3 \] Calculating \( 3^3 \) gives us \( 27 \), so: \[ (5-x)(-1-x) = 27 \] Expanding the left side: \[ -5 - 5x + x + x^2 = 27 \] Which simplifies to: \[ x^2 - 4x - 5 = 27 \] Now, moving \( 27 \) to the left side: \[ x^2 - 4x - 32 = 0 \] Next, we can solve this quadratic equation using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): Here \( a = 1, b = -4, c = -32 \): \[ b^2 - 4ac = (-4)^2 - 4(1)(-32) = 16 + 128 = 144 \] \[ x = \frac{-(-4) \pm \sqrt{144}}{2(1)} = \frac{4 \pm 12}{2} \] Calculating the two possible values for \( x \): 1. \( x = \frac{16}{2} = 8 \) 2. \( x = \frac{-8}{2} = -4 \) Now we need to check whether these values satisfy the original logarithmic conditions. For \( x = 8 \): - \( \log_{3}(5-8) \) gives a negative argument, which is not valid. For \( x = -4 \): - \( \log_{3}(5-(-4)) = \log_{3}(9) \) is valid, and \( \log_{3}(-1-(-4)) = \log_{3}(3) \) is also valid. Thus, \( x = -4 \) is the only valid solution.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy